Unraveling benzimidazole resistance in cattle gastrointestinal nematodes through Next- -Generation Sequencing - Cantón, Candela (2025)
Gastrointestinal nematodes (GIN) infection represents one of the most significant health challenges in ruminants and are the primary cause of economic losses in livestock production systems worldwide. Their control relies almost exclusively on the use of synthetic antiparasitic compounds. Inappropriate use has led to therapeutic failures associated with the development of resistant nematode parasites. The advancement in high-throughput sequencing technologies has enabled the development of molecular-based techniques for resistance diagnosis. This study describes the first molecular identification of GIN parasitizing cattle across 6 commercial farms located in Argentina, using the ITS-2 gene metabarcoding. Additionally, the fecal egg count reduction test and sequencing of the β-tubulin isotype-1 gene were used to assess benzimidazole (BZD) resistance under different anthelmintic treatment regimens (BZD alone or BZD+macrocyclic lactones). Seven GIN species were identified: H. placei (64.1%), C. punctata (26.6%), O. radiatum (3.6%) O. ostertagi (3.5%), H. contortus (1.1%), C. oncophora (0.9%) and T. axei (0.2%). Among the 21 anthelmintic treatments applied across six farms, two farms exhibited overall efficacies above 95% for all treatments, while four farms displayed efficacies below 95% for either BZD alone or combined treatments. While Cooperia punctata and Ostertagia ostertagi were the main species resistant to BZD, Haemonchus placei was found to be BZD-susceptible on all the farms. BZD resistance associated SNPs in codons 167, 198 and 200 of the isotype-1 β-tubulin gene were present in both C. puntacta and O. ostertagi, being the F200Y allele recovered with the highest frecuency. Finally, BZD resistance associated SNPs were found at low frequencies even when the in vivo FECR was >95% on the field, demonstrating the potential of β-tubulin amplicon sequencing to screen for the early emergence of resistance mutations. Monitoring the prevalence and distribution of tubulin gene polymorphisms is crucial for tracking the emergence and spread of BZD resistance, which is now being used for the first time (as a model) in the large extension cattle ranches of the Argentina ´s Pampa Húmeda.